1990
DOI: 10.1088/0022-3727/23/6/004
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced vaporisation of metal as a Riemann problem

Abstract: The process of vaporisation of a light-absorbing metal under laser irradiation is investigated from a theoretical point of view. The tools are the Euler equations, the stationary heat-flow equation and the kinetic equations to calculate the gas dynamical properties of the edge of the Knudsen layer. Using the one-dimensional deflagration theory, it is shown that the local sound velocity is an upper bound for the metal vapour velocity at the phase boundary. Furthermore, it is shown that for an absorbed intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 3 publications
4
27
0
Order By: Relevance
“…Further investigation on the dependence of  R on T s is out of the scope of this work, it may be worthwhile to mention that the asymptotic convergence at high temperature depends more or less on geometry around the considered surface point. Aden et al [29,30] theoretically analysed metal vapour expansion dynamics in 3D geometry. It was shown that with the increase of the laser intensity and that of T s ,  R approaches ~ 0.2.…”
Section: Temperature Dependence Of Pmentioning
confidence: 99%
“…Further investigation on the dependence of  R on T s is out of the scope of this work, it may be worthwhile to mention that the asymptotic convergence at high temperature depends more or less on geometry around the considered surface point. Aden et al [29,30] theoretically analysed metal vapour expansion dynamics in 3D geometry. It was shown that with the increase of the laser intensity and that of T s ,  R approaches ~ 0.2.…”
Section: Temperature Dependence Of Pmentioning
confidence: 99%
“…Experimental measurements of plume flow fields at conditions comparable to those used in this simulation are not available in the literature. In a prior simulation, Aden et al 6 solved the Euler equations, steady heat-flow equation, and the kinetic equation to calculate the gas dynamic properties at the edge of the Knudsen layer. They calculated the velocity of the metal vapor and the displaced ambient air for an absorbed laser intensity of 10 10 W m Ϫ2 .…”
Section: Numerical Modeling Study Resultsmentioning
confidence: 99%
“…He treated this layer as a gasdynamic discontinuity across which certain jump conditions expressing conservation mass, momentum, and energy. The laser-induced vaporization process of metal was also theoretically investigated by Aden et al [12], who calculated the gas dynamical properties of the edge of the Knudsen layer using the Euler equations, the stationary heat flow equation and the kinetic equations. On an assumption that a stationary limit of the vaporization process is reached, the solution of the Euler equations is equivalent to that of a Riemann problem.…”
Section: Laser-induced Ablationmentioning
confidence: 99%